Pengaruh Harga Sewa dan Kualitas Pelayanan terhadap Kepuasan Pedagang di Pasar Banyuasri - Widyantari, Ni Wayan Popy; Santi, Ni Wayan Ayu (Jurnal Pendidikan Ekonomi Undiksha, 2025)
The purpose of this research is to analyze the influence of rental price and service quality on traders’ satisfaction at Banyuasri Market. This research employs a quantitative approach with a stratified random sampling technique involving 88 active traders at Banyuasri Market. Data analysis was conducted using multiple linear regression analysis. The results of the study indicate that rental price has a positiveand significant effect on traders’ satisfaction, with a significant value of 0,000 < 0,05. Service quality also has a positive and significant effect on traders’ satisfaction, with a significance value of 0,000 < 0,05. Simultaneous analysis of the rental price and service quality variables shows a significant effect on traders’ satisfaction, as evidenced by an F-value of 115.373 > F-table of 3.10 at a significance level of 0,000 < 0,05. These results demonstrate that the independent variables have a significant effect, both partially and simultaneously, on the dependent variable, namely traders’ satisfaction at Banyuasri Market.